Structural and stratigraphic evolution of the Iberia–Newfoundland hyper-extended rifted margin: a quantitative modeling approach. - Mohn, G.; D. Karner, G.; Manatschal, Gianreto; Johnson, C. A. (Geological Society, London, Special Publications, 2015)
International audience